Invasive tracheobronchial aspergillosis progressing from bronchial to diffuse lung parenchymal lesions - Ohta, Hiromitsu (Respirol Case Rep, 2016)
Invasive tracheobronchial aspergillosis that is entirely limited or predominantly confined to tracheobronchial lesions is a relatively rare form of invasive pulmonary aspergillosis. Extended parenchymal opacities that are radiological manifestations of invasive aspergillosis sometimes occur following invasive tracheobronchial aspergillosis. However, it remains unclear whether or not invasive tracheobronchial aspergillosis is the initial stage of invasive pulmonary aspergillosis. A 61‐year‐old woman was admitted because of severe diarrhea and dehydration. Three days after admission, she complained of dyspnea. A computed tomography (CT) scan of the chest showed bronchial wall thickening. She developed respiratory failure despite antibiotic therapy. A CT scan showed obstructions of bronchial lumens and bronchiectasis in the right upper lobe. A spergillus fumigatus was identified from samples obtained in bronchoscopic examination. Bronchial lesions rapidly progressed to be extended. A spergillus infection with multiple parenchymal opacities was observed on CT scan. She responded to treatment with antifungal drugs.